If you ever want to bring an alligator to school, don't! - Parsley, Elise (New York : Little, Brown and Company, 2015)
A child provides insights, based on personal experience, into everything that can go wrong if one brings an alligator to school for show-and-tell.
Keywords: Alligators -- Fiction; Schools -- Fiction; Show-and-tell presentations -- Fiction; Humorous stories